ANALYSIS OF THE ACCURACY OF REPRODUCING THE POSITION FUNCTION BY THE MECHANISM OF THE THIRD CLASS FOR THE OSCILLATIONAL MOVEMENT OF THE EYE NEEDLE OF THE BOND KNITTING MACHINE - Дворжак, Володимир; Манойленко, Олександр; Крикун, Євгеній; Клинников, Антон (Technologies and Engineering, 2022)
Purpose. Improving methods of calculation and research of target mechanisms of machines for the fashion industry using CAD applications. Methodology. Used the apparatus of vector algebra; method of vector transformation of coordinates for kinematic calculation of plane mechanisms with structural groups of the third class; analytical method of differentiation to determine the position error of the third class mechanism with rotating kinematic pairs. Findings. The calculated expressions for determining the function of the position of the eyelets, the primary errors of the mechanism, as well as positional errors caused directly by the primary errors of the mechanism of the eyelets of the warp knitting machine, which is built on a multi-link flat mechanism with structural groups with rotating kinematic pairs, as a function of the angle of rotation of the drive crank. The error limits of the position Δmax and Δmin of the comb with eye needles in the projections on the coordinate axis and in absolute value are determined. Originality. A comparative analysis of the accuracy of the position function reproduction was performed by the synthesized six-link mechanism of the third class and the basic eight-link mechanism of the second class of the warp knitting machine. Practical Value. The procedure for calculating the accuracy of the synthesized six-link mechanism of the 3rd class with rotating kinematic pairs by the differential method for automated computer calculation in CAD programs is proposed. Software blocks for automated computer accuracy calculation in Mathcad have been created. The obtained results can be used for modeling, calculation and construction of multi-link flat mechanisms with structural groups of the 3rd class of the 3rd order with rotating kinematic pairs and similar target lever mechanisms of higher classes of machines for the fashion industry.